Overseeing Criminal Justice: The Supervisory Role of the Public Prosecution Service in China. (28th November 2017) - Mou, Yu
Abstract : The Chinese public prosecution service, the procuracy, is modelled on the Soviet Union system and has been accorded the controversial function of supervising other legal institutions in the criminal justice system. Drawing upon my own empirical data on the prosecution of crime in China, this article critically examines the way the power of supervision operates from an internal perspective. It argues that the power of supervision has been used as an institutional asset to secure the interests of the procuracy by analysing its oversight of police investigations and court decisions, the way prosecutors perceive themselves, and the efficacy of the supervision in a comparative context. The current status of the procuracy dictates that it is unable to undertake the role of supervision to safeguard the criminal process.